De Novo Synthesis of Phosphatidylcholine Is Essential for the Promastigote But Not Amastigote Stage in Leishmania major - Moitra, Samrat; Basu, Somrita; Pawlowic, Mattie; Hsu, Fong-fu; Zhang, Kai (Frontiers in Cellular and Infection Microbiology, 2021)
Phosphatidylcholine (PC) is the most abundant type of phospholipids in eukaryotes constituting 30% of total lipids in Leishmania. PC synthesis mainly occurs via the choline branch of the Kennedy pathway (choline  choline-phosphate  CDP-choline  PC) and the N-methylation of phosphatidylethanolamine (PE). In addition, Leishmania parasites can acquire PC and other lipids from the host or culture medium. In this study, we assessed the function and essentiality of choline ethanolamine phosphotransferase (CEPT) in Leishmania major which is responsible for the final step of the de novo synthesis of PC and PE. Our data indicate that CEPT is localized in the endoplasmic reticulum and possesses the activity to generate PC from CDP-choline and diacylglycerol. Targeted deletion of CEPT is only possible in the presence of an episomal CEPT gene in the promastigote stage of L. major. These chromosomal null parasites require the episomal expression of CEPT to survive in culture, confirming its essentiality during the promastigote stage. In contrast, during in vivo infection of BALB/c mice, these chromosomal null parasites appeared to lose the episomal copy of CEPT while maintaining normal levels of virulence, replication and cellular PC. Therefore, while the de novo synthesis of PC/PE is indispensable for the proliferation of promastigotes, intracellular amastigotes appear to acquire most of their lipids through salvage and remodeling.